2022
DOI: 10.1186/s13047-021-00505-4
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term results of gait analysis with the Heidelberg foot measurement method and functional outcome after operative treatment of ankle fractures

Abstract: Background Ankle fractures are common fractures in trauma surgery. Several studies have compared gait patterns between affected patients and control groups. However, no one used the Heidelberg Foot Measurement Method in combination with statistical parametric mapping of the entire gait cycle in this patient cohort. We sought to identify possible mobility deficits in the tibio-talar joint and medial arch in patients after ankle fractures as a sign of stiffness and pain that could result in a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…At 12 months after surgery, pain is mild and occasional, the ADF ROM is not complete, and restrictions are practically limited to sports and recreational activity. To date, the minimum clinically relevant difference for ankle injuries is not clearly specified, although some authors propose a difference of 6 points on the AOFAS scale [63]. Therefore, given the increase of almost 11 points between 6 and 12 months after surgery in our results, it can be considered clinically relevant.…”
Section: Discussionmentioning
confidence: 83%
“…At 12 months after surgery, pain is mild and occasional, the ADF ROM is not complete, and restrictions are practically limited to sports and recreational activity. To date, the minimum clinically relevant difference for ankle injuries is not clearly specified, although some authors propose a difference of 6 points on the AOFAS scale [63]. Therefore, given the increase of almost 11 points between 6 and 12 months after surgery in our results, it can be considered clinically relevant.…”
Section: Discussionmentioning
confidence: 83%
“…The author emphasized that the severity of the fracture is inversely proportional to the extent of joint flexion/extension. Similarly, Böpple and his colleagues ( Böpple et al, 2022 ) reported that the motion of the tibiotalar joint and medial arch in patients with ankle fractures was limited, and the regional GRF was also reduced; however, over time, significant improvement could be observed. The author also confirmed that patients with fractures were more inclined to lift their feet rather than push them off the ground during forward movement.…”
Section: Application In Foot and Ankle Diseasesmentioning
confidence: 88%
“…Consequently, the study includes standard deviation values to capture this aspect. Furthermore, this type of averaging has been performed with patients who have foot disorders, ambulation, or amputation 26 , 55 58 . However, analyzing stride data directly; i.e.…”
Section: Discussionmentioning
confidence: 99%